2003 European Control Conference (ECC) 2003
DOI: 10.23919/ecc.2003.7085323
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation of railway vehicle dynamic model using rao-blackwellised particle filter

Abstract: This paper presents the development of a new method for parameter estimation in linear state space model. The proposed method is based on a Rao-Blackwellised particle filter. The simulation results with a railway vehicle dynamic model are provided which demonstrate the effectiveness of the proposed method in comparison with the conventional EKF-based method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…If Model 4 is compared to Model 3, it can be seen that the matrices , and are independent of in Model 4, which implies that (28) This follows from (23b)-(23d) in Theorem 2.1. According to (28) only one instead of Riccati recursions is needed, which leads to a substantial reduction in computational complexity.…”
Section: B Important Model Classmentioning
confidence: 61%
See 2 more Smart Citations
“…If Model 4 is compared to Model 3, it can be seen that the matrices , and are independent of in Model 4, which implies that (28) This follows from (23b)-(23d) in Theorem 2.1. According to (28) only one instead of Riccati recursions is needed, which leads to a substantial reduction in computational complexity.…”
Section: B Important Model Classmentioning
confidence: 61%
“…According to (28) only one instead of Riccati recursions is needed, which leads to a substantial reduction in computational complexity. This is, of course, very important in real-time implementations.…”
Section: B Important Model Classmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stages of the work, a Kalman filter [27] was used to estimate a generic smooth continuous conicity parameter applied to linear equations (16) and (17). The state of the Kalman filter was augmented to include the conicity parameter so that it could be estimated, therefore making the problem non-linear and an extended Kalman filter was used.…”
Section: Conicity Estimation Through Kalman Filteringmentioning
confidence: 99%
“…Initially Li et al (2003), Li et al (2004) and Li et al (2006) showed that condition monitoring of suspension components such as secondary dampers can be achieved in real time using RaoBlackwellised Particle Filters (RBPF). This was less successful at monitoring the condition of wear of the wheelset in combination with the rail, known as a linearised effective conicity function, λ.…”
Section: Introductionmentioning
confidence: 99%